Exchange Rate Uncertainty, Forward Contracts, and International Portfolio Selection - EUN, CHEOL S.; RESNICK, BRUCE G. (Journal of Finance, 1988)
ABSTRACT In this paper, ex ante efficient portfolio selection strategies are developed to realize potential gains from international diversification under flexible exchange rates. It is shown that exchange rate uncertainty is a largely nondiversifiable factor adversely affecting the performance of international portfolios. Therefore, it is essential to effectively control exchange rate volatility. For that purpose, two methods of exchange risk reduction are simultaneously employed: multicurrency diversification and hedging via forward exchange contracts. The empirical findings show that international portfolio selection strategies designed to control both estimation and exchange risks almost consistently outperform the U.S. domestic portfolio in out‐of‐sample periods.